SYNTHESIS AND BIOLOGICAL EVALUATION OF MUTUAL PRODRUGS OF 2- [3- (TRIFLUOROMETHYL)PHENYL]AMINOBENZOIC ACID - MEENU PALIWAL, SUCHETA; RUCHITA; HIMANSHU; MONIKA; SHILPA JAIN (International Journal of Pharma and Bio Sciences, 2015)
For reducing the gastrointestinal (GI) toxicity associated with flufenamic acid (FA), its carboxylic group was masked by synthesizing its mutual prodrugs with propyphenazone by direct coupling and by using spacer technique. The structures of the synthesized mutual prodrugs (FE and FG) were confirmed by IR, 1H NMR, 13C NMR, mass spectroscopy and their purity were established by elemental analysis. In vitro hydrolysis study of both prodrugs (FE & FG) in enzyme-free simulated intestinal fluid (SIF, pH 7.4) furnished 43.97% and 53.46% release of parent drug FA with a half life of 9.13 and 7.54 hours respectively, following first order kinetics. While in simulated gastric fluid (SGF, pH 1.2) they were found to be stable. Both FA prodrugs were retaining anti-inflammatory activity intact and exhibited better analgesic activity along with much reduced ulcerogenicity as compared to parent drug. However prodrug FE showed better percentage anti-inflammatory activity (61.91%) than FG (45.22%) at the end of 6th h and it also exhibited better percentage analgesic activity (76.85%) than FG (71.12%) at the end of 2nd h. Hence FE could be considered as a better candidate for prodrug among the two.